The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/00110000221094324
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Minority International Counseling Psychology Trainees’ Experiences in Clinical Supervision

Abstract: The present study discusses clinical supervision from the perspectives of 20 international counseling psychology trainees with a focus on English-specific experiences in training. Using concept mapping, we identified four clusters of sociolinguistic experiences in clinical settings: Growth and Strength Through Embracing Vulnerability, Barriers to Showing Clinical Potential, Fear of Being Seen as Incompetent, and Self-Doubt About Therapeutic Performance and Relationships. Helpful supervisory events included sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition to training-related issues discussed in the implications for advocacy section, this section will focus on training recommendations for individual faculty advisors and supervisors. If unchecked, faculty advisors and supervisors could be susceptible to implicit biases that focus on the deficiencies of international students, which are prevalent in higher education (Garrison et al, 2022; Rhee & Sagaria, 2004). We caution faculty advisors and supervisors to safeguard themselves against such biases that potentially lead them to underestimate international counseling psychology students’ ability to achieve bicultural competence and social justice advocacy skills during their training, or to misinterpret their intention to return to their home countries after graduation as a lack of interest and/or motivation in second-culture acquisition and social justice training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to training-related issues discussed in the implications for advocacy section, this section will focus on training recommendations for individual faculty advisors and supervisors. If unchecked, faculty advisors and supervisors could be susceptible to implicit biases that focus on the deficiencies of international students, which are prevalent in higher education (Garrison et al, 2022; Rhee & Sagaria, 2004). We caution faculty advisors and supervisors to safeguard themselves against such biases that potentially lead them to underestimate international counseling psychology students’ ability to achieve bicultural competence and social justice advocacy skills during their training, or to misinterpret their intention to return to their home countries after graduation as a lack of interest and/or motivation in second-culture acquisition and social justice training.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of microaggressions in therapy, E. Yeo and Torres-Harding (2021) identified strategies to address microaggressions, such as increasing flexibility, empathy, and cultural knowledge and sensitivity. Despite training and supervision, Garrison et al (2022) found that microaggressions experienced by international counseling psychology trainees in therapy were underacknowledged or underexplored. Overall, little is known about what constitutes effective approaches other than demonstrating openness toward microaggressions.…”
Section: Racial Microaggression In Psychotherapymentioning
confidence: 99%
“…Two studies in this Special Issue focused on the clinical training of international students. Language is a common stressor for international students (e.g., Knox et al, 2013), and the work by Garrison et al (2022 [this issue]) provides an in-depth, trainee-centered understanding of the clinical supervision sociolinguistic experiences of 20 international students in counseling psychology. Using concept mapping strategies, the authors identified four language-based clusters (e.g., growth via vulnerability) in clinical settings in addition to seven respective supervisor competency clusters that assist (e.g., genuine curiosity and understanding) and limit (e.g., working from a deficit lens, limited multicultural awareness and humility) international students in their clinical development.…”
mentioning
confidence: 99%